HALAL APPROACH ON FOOD PRODUCT DESIGN IN THE VILLAGE LEVEL - Zilal Afwa Ajidin; Rika Fatimah TL (IAIN Batusangkar, 2022)
This research aims to determine the management model for halal products at the village level. The model used is the Tetrapreneur Mutual Cooperation Movement (G2R). The four approaches to this tetrapreneur are business chain, business market, business quality and business brand. The object of this research is the fried meatball products in Bejiharjo Village, Gunungkidul Regency, DI Yogyakarta. The method used is descriptive qualitative approach with in-depth interviews and literature study. The results of this study indicate that the development of food product designs at the village level can be carried out with the support of capital access, product innovation, consumer awareness, halal services, digital marketing and ancillary services.